Narrative Policy Analysis in the Congo: Implications for Resource Extraction Policy - Richardson, Kayla (Université d'Ottawa | University of Ottawa, 2020)
The Democratic Republic of the Congo, also referred to as the DRC or the Congo, is a country with vast natural resources, including water, fertile land, and profitable minerals such as copper, gold, diamonds, tantalum (coltan), tin, tungsten, cobalt, and uranium. The extractive industries have the potential to support economic growth and development and are of strategic importance to the global economy. The industry could make the Congo one of the richest countries in the world, but the Congo has been unable to reap the rewards of their abundant natural resources due to the high level of violence fuelling and fueled by extraction of mineral resources. The mismanagement of natural resource wealth in the Congo continues to contribute to the conflict in the eastern regions, which in turn prevents the state from taking control of the mineral sector in a vicious cycle (Trefon, 2016). The cause of conflict in the eastern region, the role the natural resource sector, and what can be done to prevent conflict and spur development are a matter of debate. There are differing solutions put forward including mineral tracking and certification schemes, institutional and legal frameworks, company due diligence, and organizational codes of conduct to manage the natural resource sector. How the issues of resource extraction and conflict and the solutions are being presented are a result of dominant narratives being told and re-told. The dominant narratives about the Congo often portray the country in a one-dimensional way, capturing the cause of conflict in a couple of sentences, and focus on technical interventions that can be pursued as consumers, companies, and donors, to improve the development outcomes of the Congo. Media reports speak of the cost of the ongoing conflict, citing figures of death and destruction, often focusing on the impact on victims. In the dominant narratives, policy can be used to ensure transparency and accountability in mineral supply chains to prevent rebel groups from profiting on conflict minerals or can establish certification schemes to verify ‘conflict-free’ status. Under the dominant narratives, technical solutions such as those presented will end conflict 3 over natural resources, prevent further human rights violations and could regulate the mining sector to prevent future incidents of violence (de Koning, 2011; Enough Project, 2017; Global Witness, 2009). Dominant narratives and the impact they have extend beyond the borders of the Congo. Simplistic narratives around natural resources have been around for decades, present in the literature around the natural resource curse and the connections between natural resources and conflict (Auty, 1993; Le Billon, 2014; Ross, 2003). The debates common in literature are used to inform policy, and thus have an impact on government decision-making and beyond. However, following a narrative that lacks complexity covers one aspect of a larger situation (Autesserre, 2012). Put bluntly, simple narratives have led to simple policy. Putting more complexity into policy can be easier said than done, as there is no objective truth or one “correct” narrative. The way narrative is interpreted has the potential to influence the way a subject is viewed and how it is acted upon. Having more complex narratives that challenge what has been developed as common knowledge will not necessarily translate into effective policy in the Congo, but recognizing the consequences of dominant narratives can help move the conversation forward and can limit the damages these imaginings can have.